Effects of Inorganic Fertilizers on the Growth and Production Performance of Exotic Carps in Polyculture System (Progressive Agriculture, 2013)
The present study was conducted to evaluate the effects of inorganic fertilizers in combination with constant supply of supplementary feeds on growth and production of exotic carps for a period of one year, from February 2007 to January 2008. Three treatments namely T1 {Urea + TSP (2 : 1), 40 kg/ha}, T2 {Urea + TSP (2 : 1), 60 kg/ha} and T3 (Urea + TSP (2 : 1), 80 kg/ha}, each in triplicates were used in the present study. Fertilizers were applied over the ponds fortnightly. The fishes were stocked @ 10,000 fry/ha with a combination ratio of 4 silver carp, 3 common carp and 3 grass carp. A mixture of supplementary feeds composed of rice bran, wheat bran and fish meal (40 : 40 : 20) were provided in all the treatments @ 5% body weight of fish twice daily. The average length (cm) and weight (g) gain were the highest in silver carp (32.3 ± 0.05 cm and 591 ± 1.37g) in treatment T3 and the lowest in grass carp (24.5 ± 0.05 cm and 509.5 ± 0.92 g) in treatment T1 . The highest survival rate (%) was incased for silver carp (81.25%) in treatment T3 and the lowest in grass carp (66.67%) in treatment T1 . The maximum production of all the fishes was recorded in treatment T3 (1920, 1304 and 1164 kg/ha/year respectively), followed by the treatments T2 (1766, 1176 and 1084 kg/ha/year respectively) and T1 (1684, 1108 and 1022 kg/ha/year respectively). The water quality parameters such as temperature (°C), dissolved oxygen (mg/l), pH and transparency (cm), of all the experimental ponds were found within the productive range, which is suitable for fish culture.DOI: http://dx.doi.org/10.3329/pa.v19i2.16953 Progress. Agric. 19(2): 129 - 137, 2008